5 alpha-reductase deficiency without hypospadias. Issue 10 (October 1990) - Ng, W K; Taylor, N F; Hughes, I A; Taylor, J; Ransley, P G; Grant, D B
Abstract : A boy aged 4 with penoscrotal hypospadias and his brother aged 12 with micropenis had typical changes of homozygous 5 alpha-reductase deficiency. After three injections of chorionic gonadotrophin there was a trivial rise in plasma dihydrotestosterone with a normal increase in plasma testosterone. Urine steroid chromatography showed abnormally high 5 beta: 5 alpha ratios and 5 alpha-reductase activity was appreciably reduced in genital skin fibroblasts. The results indicate that 5 alpha-reductase deficiency is not invariably associated with genital ambiguity.